Transplantation of human fetal biliary tree stem/progenitor cells into two patients with advanced liver cirrhosis - Cardinale, Vincenzo (BMC Gastroenterol, 2014)
BACKGROUND: Efforts to identify cell sources and approaches for cell therapy of liver diseases are ongoing, taking into consideration the limits recognized for adult liver tissue and for other forms of stem cells. In the present study, we described the first procedure of via hepatic artery transplantation of human fetal biliary tree stem cells in patients with advanced cirrhosis. METHODS: The cells were immune-sorted from human fetal biliary tree by protocols in accordance with current good manufacturing practice (cGMP) and extensively characterized. Two patients with advanced liver cirrhosis (Child-Pugh C) have been submitted to the procedure and observed through a 12 months follow-up. RESULTS: The resulting procedure was found absolutely safe. Immuno-suppressants were not required, and the patients did not display any adverse effects correlated with cell transplantation or suggestive of immunological complications. From a clinical point of view, both patients showed biochemical and clinical improvement during the 6 month follow-up and the second patient maintained a stable improvement for 12 months. CONCLUSION: This report represents proof of the concept that the human fetal biliary tree stem cells are a suitable and large source for cell therapy of liver cirrhosis. The isolation procedure can be carried out under cGMP conditions and, finally, the infusion procedure is easy and safe for the patients. This represents the basis for forthcoming controlled clinical trials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12876-014-0204-z) contains supplementary material, which is available to authorized users.